2014
DOI: 10.1890/es14-00145.1
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐dependent thresholds in the dominant controls of wildfire size in semi‐arid southwest Australia

Abstract: Abstract. We aimed to characterize the size distribution of naturally occurring wildfires and to determine how fuel characteristics influence wildfire size in a vegetation mosaic of shrublands and woodlands in semi-arid southwest Australia. The shape of frequency-size distributions of fires can be used to elucidate shifts in the dominant drivers or constraints of fire size. We modeled the cumulative frequencysize distribution of wildfires in southwest Australia using a segmented linear model with two break poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
(69 reference statements)
1
16
0
Order By: Relevance
“…Some authors prefer to use relative burnt area (BA) thresholds [25][26][27][28] but most of the definitions are based on absolute quantitative thresholds which can change in the course of time, as well as with the geographic area of reference [28,29]. In Europe, thresholds for LFs that have been proposed range from ≥ 100 ha (e.g., [30][31][32][33][34][35][36][37]) to ≥ 1000 ha [38].…”
Section: Large Very Large and Extremely Large Firesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors prefer to use relative burnt area (BA) thresholds [25][26][27][28] but most of the definitions are based on absolute quantitative thresholds which can change in the course of time, as well as with the geographic area of reference [28,29]. In Europe, thresholds for LFs that have been proposed range from ≥ 100 ha (e.g., [30][31][32][33][34][35][36][37]) to ≥ 1000 ha [38].…”
Section: Large Very Large and Extremely Large Firesmentioning
confidence: 99%
“…In other regions in the world, the threshold ranges from the minimum values of ≥ 20 ha in Arizona (U.S.) [39], to 1,000 ha in Australia [40], to 4,950 ha in Boreal Shield ecozone of Ontario [41] and to 40,000 ha in the Western United States [42]. The highest thresholds found for a LF were for Eastern Australia with > 41,020 ha [29], for North Australia with > 100,000 ha [43]; for Australia values of 10 6 ha were considered by Gill and Allan [27].…”
Section: Large Very Large and Extremely Large Firesmentioning
confidence: 99%
“…Fire activity is more dependent on suitable weather and drought conditions where fuels are plentiful and recover quickly after disturbance, whereas in less productive regions, it is regulated by fuel amount and connectivity [74]. A study by O'Donnell et al [75] provides a vivid example of a fuel-limited fire regime: semi-arid mediterranean shrublands and woodlands in the 1.5 million ha Lake Johnston region of South-Western Australia, that rarely burns within 20 years of the last fire, regardless of fire size and even under extreme fire weather conditions.…”
Section: Wildfires As Fuel Treatmentsmentioning
confidence: 99%
“…Several studies have suggested that there are scale-related thresholds or breakpoints in fire behaviour which reflect changes in the main drivers of fire behaviour and which require different management to counter that behaviour (Boer et al, 2008;Liu et al, 2013;O'Donnell et al, 2014;Peters et al, 2004;Ricotta et al, 2001;Slocum et al, 2010). Much of the evidence comes from identifying distinct phases in the frequency distribution of fire size (Boer et al, 2008;McKenzie and Kennedy, 2012;O'Donnell et al, 2014;Pueyo, 2007;Ricotta et al, 2001). Peters et al (2004) defined four thresholds for a fire: initiation, spread within a fuel patch, among fuel patches and 'blow-up' that demarcate major shifts in the drivers of fire behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2013) found that for 146 fires in Boreal China, fuel and topography were most important in determining the final size of small fires, but weather was more important for larger fires. O'Donnell et al (2014) compared the selectivity of different vegetation types among 60 small and large fires and concluded that large fires occur when wet years drive fuel growth in woodlands that normally do not have sufficient fuel connectivity to burn.…”
Section: Introductionmentioning
confidence: 99%